Design and Implementation Process Of Mind Mapping Method In PAI Learning - Hamdani, Moh. Fauzan; Rahman, Arif (Early Publishing, 2025)
This study aims to thoroughly describe, analyze, and map the pedagogical design and implementation process of the mind mapping method in Islamic Religious Education (PAI) learning at SD Negeri Pendrikan Lor 01 Semarang. This research employs a qualitative field research methodology with a descriptive-analytical approach. Data collection techniques were systematically carried out through passive participatory observation of classroom dynamics, structured in-depth interviews with PAI teachers and fourth-grade students, and documentation of lesson plans (RPP) as well as students' mind mapping portfolios. The interactive model of analysis by Miles and Huberman was utilized to ensure rigorous data processing. The results show that the implementation of mind mapping is structured into three integrated phases: first, the preparation stage, which involves designing specialized lesson plans and identifying appropriate materials; second, the execution stage, where students collaborate in groups using visual triggers such as colors, branches, and symbols to map the materials; and third, the product-and-process evaluation stage. Integrating this method successfully shifts the learning paradigm from passive memorization to an active-constructivist model, matching the cognitive development of elementary school-aged children.